Logística reversa: conceito e a importância da logística reversa no âmbito empresarial e os aspectos positivos que ela traz para a empresa e sociedade - DESSIMONI, Leonardo Maikon (119, 2021)
Neste trabalho será apresentado, à evolução e o avanço da Logística Reversa, assim como, o referencial teórico. Está área está em constante evolução tanto no Brasil quando no mundo, por ser um diferencial perante aos concorrentes e por regulamentar o retorno dos materiais (insumos e resíduo). Com a aplicação da logística reversa na organização, controla as informações necessárias ao ciclo produtivo, agregando valores econômicos, ecológicos e logísticos.

In this work, the evolution and advancement of Reverse Logistics will be presented, as well as the theoretical framework. This area is in constant evolution both in Brazil and in the world, as it is a differential against competitors and because it regulates the return of materials (inputs and waste). With the application of reverse logistics in the organization, it controls the information necessary for the production cycle, adding economic, ecological and logistical values.
Reverse logistics: concept and importance of reverse logistics in the business environment and the positive aspects it brings to the company and society
Keywords: Logística reversa; Gestão e Negócios